Transport planning for sustainable communities - Lucas, K; Halden, D; Wixey, S (Earthscan Publications, 2010)
This groundbreaking new volume on social sustainability offers both critique and creative solutions. It challenges the conventional wisdoms of social sustainability and presents practical examples of projects that will help practitioners to think carefully and innovatively about the situations they are addressing. The book consists of original contributions from academics working in the fields of urban planning, housing, regeneration, transport and international sustainable development. Drawing on case study research gathered in the UK, Europe and Africa, it adopts an original, interdisciplinary approach to both theory and practice, illustrating the challenges and opportunities facing policy-makers and practitioners attempting to develop, manage and maintain sustainable communities. The authors argue that the dominant approach of 'how to do' small scale social sustainability fails to locate it within broader social processes. Ignoring the context not only sustains, but also actively reproduces wider inequalities. The book presents a new, more coherent and more complete approach to issues of social sustainability in urban areas. The book approaches current urban policy discourses in three different ways, represented by three sections: firstly focusing on small places within the urban fabric, secondly addressing the whole urban fabric by examining whether changing urban living and working patterns. The third section explores some of the ways that funding can be secured to achieve the aims of social sustainability and the social planning associated with it.